An emergent clade of SARS-CoV-2 linked to returned travellers from Iran. Issue 1 (10th April 2020) - Eden, John-Sebastian; Rockett, Rebecca; Carter, Ian; Rahman, Hossinur; de Ligt, Joep; Hadfield, James; Storey, Matthew; Ren, Xiaoyun; Tulloch, Rachel; Basile, Kerri; Wells, Jessica; Byun, Roy; et al.
Abstract: The SARS-CoV-2 epidemic has rapidly spread outside China with major outbreaks occurring in Italy, South Korea, and Iran. Phylogenetic analyses of whole-genome sequencing data identified a distinct SARS-CoV-2 clade linked to travellers returning from Iran to Australia and New Zealand. This study highlights potential viral diversity driving the epidemic in Iran, and underscores the power of rapid genome sequencing and public data sharing to improve the detection and management of emerging infectious diseases.